Enterohepatic Migration of Fish Bone Resulting in Liver Abscess. (8th November 2015) - Ede, Chikwendu; Sobnach, Sanju; Kahn, Delawir; Bhyat, Ahmed
Abstract : Liver abscess formation due to enterohepatic migration of a foreign body is extremely rare. Foreign body ingestion is generally an unconscious and painless event, thus complicating preoperative diagnosis in most patients. We report the case of a 61-year-old man who presented with secondary peritonitis from a ruptured hepatic abscess after an ingested fish bone migrated into the liver.